Candida spp. adherence to oral epithelial cells and levels of IgA in children with orthodontic appliances - Célia Regina Gonçalves e Silva; Luciane Dias de Oliveira; Mariella Vieira Pereira Leão; Antonio Olavo Cardoso Jorge (Brazilian Oral Research, 2014)
Adhesion and colonization of the oral cavity by Candida albicans is an initial step in candidosis. Orthodontic and other oral appliances seem to favor candidal presence. The aim of this work was to compare the presence of Candida species in saliva, their adherence to oral epithelial cells, and the levels of anti-C. albicans IgA in children with or without orthodontic appliances. This study included 30 children 5 to 12 years old (9.1 ± 1.7 years old) who were users of removable orthodontic devices for at least 6 months and 30 control children of similar ages (7.7 ± 1.5 years old). The presence of yeast species in the saliva was evaluated by microbiological methods. Candida species were identified using phenotypic methods. Anti-C. albicans IgA levels in saliva were analyzed by ELISA. The yeasts adhering to oral epithelial cells were assessed by exfoliative cytology. No statistically significant differences were observed for saliva yeast counts and anti-C. albicans IgA levels between the studied groups. Children with orthodontic devices exhibited more yeast cells adhering to oral epithelial cells and a higher percentage of non-albicans species relative to the control group. In conclusion, orthodontic appliances may favor the adherence of Candida to epithelial cells but do not influence the presence of these yeasts in saliva, and the levels of anti-C. albicans IgA do not correlate with yeast adherence or presence of Candida in the oral cavity